Gas Separation Membranes - Ismail, Ahmad Fauzi (Springer, 2015)
This book describes the tremendous progress that has been made in the development of gas separation membranes based both on inorganic and polymeric materials. Materials discussed include polymer inclusion membranes (PIMs), metal organic frameworks (MOFs), carbon based materials, zeolites, as well as other materials, and mixed matrix membranes (MMMs) in which the above novel materials are incorporated. This broad survey of gas membranes covers material, theory, modeling, preparation, characterization (for example, by AFM, IR, XRD, ESR, Positron annihilation spectroscopy), tailoring of membranes, membrane module and system design, and applications. The book is concluded with some perspectives about the future direction of the field.